Efficacy of High and Low Dose of BCG and Their Complications in Superficial Transtional Cell Carcinoma of Urinary Bladder - Muhammad Umer, Faisal Shabbir, Ammad Ahmad Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bladder cancer patients mostly (75%) present with non-muscle invasive bladder tumors. Aim: To compare tumor recurrence and side effects between high and low dose of BCG in NMIBC. Study Design: Randomized controlled trial. Methodology: Patients (n=30 each group) were enrolled with expected percentage of side effects with low dose (40 mg) as 2.5 % and high dose (80 mg) as 25.8%. Patients of all age groups with both genders having NMIBC (Ta, T1, Tis) and high grade tumors (G3) determined on histopathology of TURBT sample. Patients with history of renal transplant and chemotherapy were excluded. The difference between both groups was analyzed using Chi Square test with P- value of < 0.05 was considered statistically significant. Results: The mean age of patients in group A was 55.83 ± 9.17 and group B was 59.17 ± 8.13 years. There was no significant difference in the age of two groups (P= 0.142). There was no difference in gender distribution in two groups (P=0.688). Regarding the stage of tumor there were 13 cases of stage Ta and T1 in both groups. Conclusion: It was concluded that 40 mg dose of intra-vesical BCG in patients with NMIBC had lower recurrence and side effects as compared to higher dose of intra-vesical BCG.